EFFECTS OF RAYLEIGH NUMBER, LENGTH AND THICKNESS OF CONTINENT ON TIME OF MANTLE FLOW REVERSAL - Bobrov A.M.; Trubitsyn V.P.; Jacoby W. (My University, 1998)
Numerical experiments are carried out to study the effects of continents on the structure of thermal convection in the mantle. The mantle is modelled by a viscous fluid occupying a horizontally extended rectangular 2-D region of aspect ratio 10:1. Continents are treated as thick rigid heat-conducting plates placed in the mantle, with free-slip and with no-slip conditions. Continents restrict the heat release from the underlying mantle; the mantle material heats up and becomes lighter; as a result, a hot upwelling flow replaces downwelling. We calculate the characteristic time τ of this restructuring for various values of model parameters and obtain analytical approximations for τ as function of Rayleigh number Ra, plate length L, and plate thickness d. For commonly accepted mean parameters of the Earths mantle, giving Ra=107, with continental plate thickness about 300 km and length about 6000 km, the restructuring time τ is estimated as 2·108 a. As the continents are not fixed, but drift, the possibility of forming an ascending mantle flow exists if the continent does not significantly shift during an interval of about τ relative to the mantle by more than half of its length. Hence, under a continent drifting relative to the mantle with speed less than 1 cm⧹a an ascending mantle flow is expected, whereas under rapidly moving continents such an ascending flow has not enough time to develop.